DEVELOPMENT PLAN FOR 40 CITIES EQUIVALENT TO JAKARTA IN INDONESIA IN 5 YEARS (BETWEEN PLANS AND DISCOURSE) - Ade Risna Sari; Mohammad Sawir; Heppi Syofya; Rachmawati Novaria; Barlian (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research began with the statement of Vice Presidential Candidate number one during the first Vice Presidential Candidate debate. This research aims to analyze the possibilities of development plans for 40 cities whether they are realistically implemented or not. If it is realistic then it can be categorized as a plan and if it is not realistic the tomb can be categorized as mere discourse. This research is qualitative research with an explanatory approach. The data used in this research is secondary data that researchers obtained from trusted websites, scientific journals, books and other reliable sources. The analysis technique in this research uses descriptive analysis techniques by describing whether the development policies of 40 cities equivalent to Jakarta are realistic or no. These data were analyzed using the stages of data collection, data reduction, data reflection, data analysis, and drawing conclusions (Abdurahman, 2016). This researcher analyzed the development intentions of 40 cities equivalent to Ajarta from two aspects, namely HDI and GRDP.